PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN DIVIDEND PAYOUT RATIO TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Barang Konsumsi yang terdaftar di BEI Tahun 2017-2019) - Agus Gunawan; Moh. Amin; Hariri Hariri (Universitas Islam Malang, 2021)
This study aims to determine the partial and simultaneous effect of Profitability, Liquidity, Leverage, Dividend Payout Ratio variables on the value of manufacturing companies in the goods sector listed on the IDX in 2017-2019. This study uses 4 independent variables, namely Profitability, Liquidity, Leverage and Dividend Payout Ratio and 1 dependent variable, namely Firm Value. The data used in this study is data sourced from the Indonesia Stock Exchange. The sampling technique used is purposive sampling, which is a technique where researchers can determine the number of samples used based on certain criteria. The number of samples used as many as 31 companies. The test results show that partially the Profitability, Liquidity and Dividend Payout Ratio variables have a significant effect on Firm Value while the Leverage variable has no significant effect. Based on the simultaneous test, the variables of Profitability, Liquidity, Leverage, Dividend Payout Ratio showed a significant influence on the Firm Value variable. The coefficient of determination obtained from the test results shows the influence of the independent variable on the dependent variable of 41.3%. While the remaining 58.7% is influenced by other variables outside the study. Keywords: Profitability, Liquidity, Leverage, Dividend Payout Ratio, Firm Value